First batch of PKLI-ECRL to register at UMP - Norhidayah, Mohamad (2017)
21 diploma graduates and 29 graduate graduates from various higher education institutions nationwide enrol for the ECRL Industrial Skills Training Program (PLKI-ECRL) at Universiti Malaysia Pahang (UMP) conducted by Malaysian Rail Link Company (MRL). They are the first batch intake to undergo the training to improve the skills as well as to gain experience in rail industry in this country.